Clinical Implications and Correlates of Q Waves in Patients With ST‐Elevation Myocardial Infarction Treated With Fibrinolysis: Observations from the CLARITY‐TIMI 28 Trial - Waks, Jonathan W. (Clin Cardiol, 2014)
BACKGROUND: The relationships between Q waves that appear during the acute phase of ST‐elevation myocardial infarction (STEMI), clinical characteristics, ST‐segment resolution (STRes), and clopidogrel therapy in patients treated with fibrinolysis are not well described. HYPOTHESIS: We hypothesized that Q waves would be associated with less successful reperfusion and increased cardiovascular events. METHODS: In the CLARITY‐TIMI 28 trial, 3491 STEMI patients treated with fibrinolysis were randomized to clopidogrel or placebo. Electrocardiograms were evaluated for STRes post‐fibrinolysis and the presence of pathologic Q waves during the index hospitalization in 3322 patients. RESULTS: Q waves were identified in 2045 patients (61.6%) prior to discharge and were associated with increased odds of congestive heart failure (CHF) (adjusted odds ratio [OR(adj)]: 2.10, P = 0.002) or the composite of cardiovascular death/CHF at 30 days (OR(adj): 2.08, P ≤ 0.001). Q waves were associated with lower odds of Thrombolysis in Myocardial Infarction [TIMI] flow grade 2 to 3 (OR(adj): 0.78, P = 0.028), TIMI myocardial perfusion grade 3 (OR(adj): 0.83, P = 0.029), and complete STRes at 90 minutes (OR(adj): 0.80, P = 0.030). Patients with both a Q wave and incomplete STRes 90 minutes after fibrinolysis were at higher risk for cardiovascular death or CHF (11.1%) than patients with no Q wave and at least partial STRes (1.9%). Overall, clopidogrel tended to be equally or more effective in patients without Q waves compared to those with Q waves. CONCLUSIONS: Among STEMI patients treated with fibrinolysis, evaluating for Q waves prior to discharge is a simple method of assessing for less successful reperfusion and an increased risk of adverse 30‐day cardiovascular outcomes. The combination of Q waves and 90‐minute STRes allows additional risk refinement.